Conceptual foundations of quantum field theory (Cambridge University Press, 2004)
Quantum field theory is a powerful language for the description of the subatomic constituents of the physical world and the laws and principles that govern them. This book contains up-to-date in-depth analyses, by a group of eminent physicists and philosophers of science, of our present understanding of its conceptual foundations, of the reasons why this understanding has to be revised so that the theory can go further, and of possible directions in which revisions may be promising and productive. These analyses will be of interest to graduate students and research workers in physics who want to know about the foundational problems of their subject. The book will also be of interest to professional philosophers, historians and sociologists of science, because it contains much material for metaphysical and methodological reflections, for historical and cultural analyses, and for sociological analyses of the way in which various factors contribute to the way the foundations are revised.